Analisis Kinerja Putaran Balik (U-Turn) pada Ruas Jalan Raya Taman Sidoarjo - Fahmi, Muhammad Harisul; Hartatik, Nurani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Jalan Raya Taman is located in Taman Subdistrict, Sidoarjo Regency, East Java Province, which has a section length of ±8KM with a 4/2 T type which is the main route for traffic flow. Along Jalan Raya Taman there are business, commercial and densely populated areas which affect traffic flow and are prone to vehicle build-up. The U-Turn facility on Jalan Raya Taman cannot fully overcome the problem of conflict, because the more vehicles that use the U-Turn facility at the same time or close together will cause a queue of vehicles making the U-Turn and cause traffic jams. in the same or opposite direction. The aim of this research is to determine the average volume of vehicles using the U-Turn facility on Jalan Raya Taman. This research method was carried out quantitatively using the 2023 Indonesian Road Capacity Guidelines (PKJI). The results of this research concluded that the highest Skr value for the volume of vehicles making a U-Turn at the U-Turn facility on Jalan Raya Taman, Sidoarjo was obtained by U-Turn 1 on Monday. with a value of 1188.00 Skr/hour and U-Turn 2 on Tuesday with a value of 1089.50 Skr/hour.